2022
DOI: 10.3390/foods11081130
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Sensory Profile of Durum Wheat Pasta Enriched with Carrot Waste Encapsulates

Abstract: Consumer knowledge about pasta quality differs around the world. Modern consumers are more sophisticated compared to past times, due to the availability of information on pasta types and quality. Therefore, this study investigated the nutritional, physical, textural, and morphological quality of durum wheat pasta enriched with carrot waste encapsulates (10 and 20% freeze-dried encapsulate (FDE) and 10 and 20% spray-dried encapsulate (SDE)), as well as determining consumer preferences for this type of product. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Utilising species/subspecies/accessions differing in their enzymatic activity or their esterification ability could be useful for producing foods with improved technological and nutritional quality features [ 43 , 131 ]. However, other approaches to increase carotenoids and tocols stability were also proposed, such as the enrichment of pasta with encapsulated carrot waste extracts in oil [ 177 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilising species/subspecies/accessions differing in their enzymatic activity or their esterification ability could be useful for producing foods with improved technological and nutritional quality features [ 43 , 131 ]. However, other approaches to increase carotenoids and tocols stability were also proposed, such as the enrichment of pasta with encapsulated carrot waste extracts in oil [ 177 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, researchers have developed pasta with various bioactive ingredients, such as: Moringa oleifera pod powder [ 168 ]; Purslane [ 172 ]; Soy okara [ 167 ]; Stinging nettle [ 169 ]; Fermented quinoa flour [ 170 ]; Potato and pigeonpea flour [ 178 ]. Carrob flour [ 176 ] Mushroom powder [ 171 , 180 ]; Brewers spent grain [ 173 , 174 ]; Carrot waste encapsulates [ 177 ]; Olive pomace [ 179 ]; Fish raw material [ 165 ]; Micro and macroalgae [ 166 , 175 , 181 , 182 , 183 , 184 ]. …”
Section: Resultsmentioning
confidence: 99%
“…It helps to visually elaborate the minute changes, occurring as a result of blends and processing techniques applied, which lead to change in the overall product quality. 12 Effect of different blends of seed flour of amaranth, green pea flour and different additives on pasta was studied by SEM and found that continuous protein network covered the starch granules in the blend containing additives. 13 Artificial neural networks (ANNs) are frequently being implemented in wide range of research fields but their applicability has been less explored in the field of food technology.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) is an authentic technique to look for variations in the texture of food product due to different processing and blends at microscopic scale. It helps to visually elaborate the minute changes, occurring as a result of blends and processing techniques applied, which lead to change in the overall product quality 12 . Effect of different blends of seed flour of amaranth, green pea flour and different additives on pasta was studied by SEM and found that continuous protein network covered the starch granules in the blend containing additives 13 …”
Section: Introductionmentioning
confidence: 99%
“…Another approach to issues regarding substitution limits is described in a report on pasta enriched with encapsulated carrot waste; this waste is rich in carotenoids, and the encapsulation protects the pigments from thermal degradation. This resulted in pasta with significantly improved protein, fat, and ash contents [ 14 ]. An alternative approach to substituting semolina to create novel health-promoting pasta is the genetic manipulation of the starch and protein composition and modification of the hardness of durum wheat in order to improve its nutritional and technological value and expand its utilization for application to a wider range of end products.…”
mentioning
confidence: 99%